Electrometric investigations on formation of lanthanum molybdates as a function of Ph - Prasad Shiva; Leite Valderí D.; Santana Renato A.C. de; Brito Joelma B. (Journal of the Brazilian Chemical Society, 2004)
The precise nature of the reaction between lanthanum nitrate and sodium molybdate at specific pH levels 7.6, 5.5 and 4.1 has been studied by means of electrometric techniques involving potentiometric and conductometric titrations, in aqueous and alcoholic media using each reagent as titrant. Well-defined breaks and inflections in the titration curves provide cogent evidence for formation and precipitation of lanthanum normal-La2O3.3MoO3, para- La2O3.7MoO3 and octa-2 La2O3.24MoO3 molybdates in the vicinity of pH 5.9, 4.8 and 4.2, respectively. Analytical investigations of the precipitates of lanthanum molybdates have also been carried out, which substantiate the results of the electrometric study.